Preparation and Properties of Hydrophobically Modified Nano-SiO(2) with Hexadecyltrimethoxysilane - Xu, Bingbing (ACS Omega, 2021)
[Image: see text] As a common inorganic silicon material, nano-SiO(2) is extremely hydrophilic due to the presence of a large number of hydroxyl groups on its surface, which limits its application in some fields. In this research, hexadecyltrimethoxysilane (HDTMS) was used to modify nano-SiO(2), and the results of water contact angle (WCA), Fourier transform infrared (FTIR), two-dimensional correlation spectroscopy (2D-COS), thermogravimetric (TG) analysis, and scanning electron microscopy (SEM) indicated that the hydrophobic long-chain alkyl of HDTMS was successfully grafted onto the surface of nano-SiO(2). When the ratio of nano-SiO(2) and HDTMS was 0.25:1, the WCA of nano-SiO(2) modified with HDTMS (HDTMS-nano-SiO(2)) reached 170.9°, which was about 5.62 times higher than that before modification, and the superhydrophobic property was obtained. The novelty of this work lies in the modified nano-SiO(2) with a WCA of over 170° and the analysis of the modification mechanism with the help of 2D-COS. This study can provide a reference for the hydrophobic modification of nano-SiO(2) and its application field expansion.